Musically Cued Gait-Training Improves Both Perceptual and Motor Timing in Parkinson’s Disease - Benoit, Charles-Etienne; Dalla Bella, Simone; Farrugia, Nicolas; Obrig, Hellmuth; Mainka, Stefan; Kotz, Sonja A. (Frontiers in Human Neuroscience, 2014)
It is well established that auditory cueing improves gait in patients with Idiopathic Parkinson’s Disease (IPD). Disease-related reductions in speed and step length can be improved by providing rhythmical auditory cues via a metronome or music. However, effects on cognitive aspects of motor control have yet to be thoroughly investigated. If synchronization of movement to an auditory cue relies on a supramodal timing system involved in perceptual, motor and sensorimotor integration, auditory cueing can be expected to affect both motor and perceptual timing. Here we tested this hypothesis by assessing perceptual and motor timing in 15 IPD patients before and after a four-week music training program with rhythmic auditory cueing. Long-term effects were assessed one month after the end of the training. Perceptual and motor timing was evaluated with the Battery for the Assessment of Auditory Sensorimotor and Timing Abilities (BAASTA) and compared to that of age-, gender-, and education-matched healthy controls. Prior to training, IPD patients exhibited impaired perceptual and motor timing. Training improved patients’ performance in tasks requiring synchronization with isochronous sequences, and enhanced their ability to adapt to durational changes in a sequence in hand tapping tasks. Benefits of cueing extended to time perception (duration discrimination and detection of misaligned beats in musical excerpts). The current results demonstrate that auditory cueing leads to benefits beyond gait and support the idea that coupling gait to rhythmic auditory cues in IPD patients relies on a neuronal network engaged in both perceptual and motor timing.